(untitled) (Panacea Journal of Medical Sciences, 2024)
Background: Diabetes mellitus is a multifactorial, multisystemic, and chronic low-grade metabolic condition. Neutrophil to lymphocyte ratio (NLR) is a basic and novel parameter to assess underlying inflammation and diabetic control levels. This study aimed to compare the values of NLR between type 2 diabetes mellitus cases and normal healthy individuals. Also, to establish a possible correlation, if any between NLR and Glycated hemoglobin A (HbA1c). Materials and Methods: This case-control study included 100 cases of type 2 diabetes mellitus patients and similar age & sex-matched healthy controls. The NLR in type 2 diabetic patients and healthy controls were compared to find a possible correlation between NLR and HbA1c levels. Results : The mean NLR in type 2 diabetes mellitus patients (mean= 4.56±1.3) in comparison with the mean NLR of healthy controls (mean= 1.94±0.95) was found to be significantly elevated (p < 0> Conclusion : An elevated NLR in individuals with no pre-existing health conditions could potentially signify compromised glucose metabolism and ongoing low-level inflammation. Additionally, when paired with HbA1c, it serves as a dependable indicator of diabetes management in type 2 diabetes mellitus patients. NLR testing is a secure, uncomplicated, and budget-friendly method that is widely available and can be employed to track the advancement of diseases, ultimately lessening the risk of complications and fatalities.